Developing leadership as a trainee- opportunities, barriers and potential improvements - Doherty, Rachel (Ulster Med J, 2018)
The General Medical Council explicitly state that doctors completing training should demonstrate capabilities in leadership and teamwork.(1) However, most trainees receive little formal training in leadership. In March 2017, at the Faculty of Medical Leadership and Management (FMLM) Northern Ireland Regional Conference, a workshop on developing leadership skills as a trainee was hosted and the views of doctors in training regarding current opportunities, potential barriers and improvements were sought. In Northern Ireland presently there are a number of opportunities available for trainees to gain experience in leadership – both by learning through observation and learning through experience. These range from informal activities which do not require significant time commitment to focused, immersive leadership experiences such as ADEPT (Achieve Develop Explore Programme for Trainees)(2), and the Royal College of Physicians’ Chief Registrar scheme.(3) Several barriers to developing leadership have been identified, including limited understanding of what constitutes leadership, a lack of senior support and little formal recognition for trainees leading teams. Time pressures, frequently rotating jobs, limited resources and difficulty upscaling can also undermine the sustainability of improvement and other leadership projects. Incorporating awareness of and training in leadership skills, as well as greater engagement with senior leaders and managers, at an early stage in training could promote understanding and encourage trainees. Formalising leadership roles within training posts may improve experience. Deaneries and Trusts can also enable leadership opportunities by facilitating study leave, raising awareness amongst supervisors, and providing career enhancing incentives for interested trainees.